2021
DOI: 10.1021/acsnano.0c10768
|View full text |Cite
|
Sign up to set email alerts
|

Highly Thermally Conductive 3D Printed Graphene Filled Polymer Composites for Scalable Thermal Management Applications

Abstract: Efficient thermal transportation in a preferred direction is highly favorable for thermal management issues. The combination of 3D printing and two-dimensional (2D) materials such as graphene, BN, and so on enables infinite possibilities for hierarchically aligned structure programming. In this work, we report the formation of the asymmetrically aligned structure of graphene filled thermoplastic polyurethane (TPU) composites during 3D printing process. The as-printed vertically aligned structure demonstrates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
122
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(124 citation statements)
references
References 53 publications
1
122
1
Order By: Relevance
“…As AM processes and technologies continue to evolve, new materials and post-processing techniques are expected to develop for high thermal conductivity metallic and polymer composite prints. Recent research on polymer composites and 2D materials such as graphene and boron nitride has shown the potential to preferably align the orientation of particles by finely controlled printing parameters, improving through-plane thermal conductivity [102].…”
Section: Advances In Science and Technology To Meet Challengesmentioning
confidence: 99%
“…As AM processes and technologies continue to evolve, new materials and post-processing techniques are expected to develop for high thermal conductivity metallic and polymer composite prints. Recent research on polymer composites and 2D materials such as graphene and boron nitride has shown the potential to preferably align the orientation of particles by finely controlled printing parameters, improving through-plane thermal conductivity [102].…”
Section: Advances In Science and Technology To Meet Challengesmentioning
confidence: 99%
“…Both structures had the same boundary convection and radiation conditions to minimize their influence on thermal conduction. [ 55 ] In addition, the top surface temperature of both models was set to the same value as suspending VA‐PG (42 °C; Figure S16B, Supporting Information) to study the transient thermal transfer process (Figure 4B). Owing to the high thermal conductivity, VA‐PG showed a faster heat transfer process, and the corresponding bottom temperature could reach ≈42 °C within 60 min (Figure 4C).…”
Section: Resultsmentioning
confidence: 99%
“…A graphene–polymer resin octet-truss lattice was used for 3D printing using stereolithography techniques [ 188 ]. Asymmetrically aligned structure of graphene thermoplastic polyurethane (PU) composites was utilized for 3D printing [ 189 ]. Graphene–polybutylene terephthalate composites have also been used for 3D printing [ 190 ].…”
Section: Applicationsmentioning
confidence: 99%